Exploring Health Development Aid and Anthropogenic Stress as Drivers of Under-Five Malaria Mortality in Nigeria with Domestic Public Health Spending as a Moderator: A Bootstrap ARDL Analysis - Bruce Iortile Iormom (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
Background: Malaria remains a going health concern, particularly in Nigeria, where under-5 mortality related to the disease continues to undermine human capital development. Despite sustained inflows of development assistance for health, progress in reducing malaria-related child mortality has not been proportional. This study is important because it evaluates whether development assistance, domestic government health expenditure, and anthropogenic environmental stress jointly shape under-5 malaria mortality outcomes in Nigeria. Aims: This study investigates the short-run and long-run effects of development assistance for health and anthropogenic environmental stress on under-5 malaria mortality in Nigeria. It further determines the moderating role of domestic government health expenditure, while controlling for income and urbanization. Methods: The study uses quarterly time-series secondary data for Nigeria from 2000 to 2022, obtained from reputable sources. The Bootstrap Autoregressive Distributed Lag approach is employed to test for the existence of a long-run cointegrating relationship and to distinguish short-run and long-run dynamics among under-5 malaria deaths development assistance for health, anthropogenic stress and domestic government health expenditure. In addition, the study employs the Toda-Yamamoto causality procedure is to correctly isolate the direction of causality among the variables. Results: The cointegration among the variables is confirmed using the Bootstrap ARDL results. Development assistance for health is found to be associated with higher under-5 malaria mortality in the long-run estimates both in the short- and long-run, and its interaction with domestic government health expenditure further strengthens this effect. Domestic government health spending independently decreases malaria deaths. However, Anthropogenic stress also increases malaria mortality risk over time, same as urbanization. The Toda-Yamamoto causality results indicate unidirectional causality running from under-5 malaria mortality to development assistance for health, suggesting that increased aid inflows is a response to increased under-5 malaria deaths rather than the cause. Conclusion: The findings show that while domestic government health expenditure contributes to reducing under-5 malaria mortality in Nigeria, development assistance for health is associated with higher mortality and appears to reinforce adverse outcomes when interacting with domestic spending. Improved coordination between foreign health aid and domestic health spending, alongside more targeted and efficiency-oriented interventions, is necessary to reduce under-5 malaria mortality in Nigeria.